Analysis Of Income And Feasibility Of Shallot Farming In Tiworo District, West Muna Regency - Sitti Nurhalizah; Azhar Bafadal; Rosmawaty, Rosmawaty (International journal of technology and education research, 2024)
This research is motivated by shallotf armersin Tikep District, West Muna Regency, currently focusing on the agricultural development sector with consideration of the condition of facilities and infrastructure that are still inadequate and hinder the development process of shallot production. Shallot production in Wulanga Jaya Village over the past few years has fluctuated and can be said to be very far from the national shallot production standard. This study aims to (1) determine the income level of shallot farmingin Tikep District, West Muna Regency, (2) determine the feasibility of shallot farmingin Tikep District, West Muna Regency. The population in this study is all onion farmers in Tikep District, West Muna Regency, which is 17 farmers. The sampling technique uses the census method, where all populations in the study are used as samples. The data analysis used is the R/Cratio. Based on the results of research on the Analysis of Income and Feasibility of Shallot Farming in Wulanga Jaya Village, Tikep District, West Muna Regency, it shows that (1) the income level of shallot farmingis 1,501.17 kg with an average income of Rp.13,368,280.73 for three planting periods where in one planting period equal to three months, three planting periods mean three harvests a year (2) The feasibility of shallot farming obtained an R/C Ratio value of 9.44 forthree planting periods where in one planting period equal to three months, three planting periods mean three harvests a year, meaning that farming is feasible to cultivate.